TEACHER-STUDENT COMMUNICATION IN PREVENTING BULLYING BEHAVIOR AMONG STUDENTS AT PLUMBUNGAN ELEMENTARY SCHOOL - Herlambang, Alvian Zidane; Rochmaniah, Ainur (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study examines the forms of communication enacted by teachers and students in the prevention of bullying at SDN Plumbungan. Bullying, as a persistent social issue in primary schools, affects students’ psychological well-being and social development. Communication serves as a central mechanism for fostering supportive relationships and minimizing social conflict. Method: This qualitative case study employed in-depth interviews, participatory observation, and documentation as data collection techniques. Informants were selected purposively, consisting of teachers and upper-grade students (fifth and sixth grades) involved in the school’s anti-bullying initiatives. Results: Findings reveal that bullying prevention is facilitated through two primary communication patterns: interpersonal and group-based. Teacher-student interpersonal communication is characterized by five key indicators, openness, empathy, supportiveness, positivity, and equality. Group communication, meanwhile, is marked by active student participation, clarity of information, responsiveness to reports, collective emotional support, and constructive feedback. These communication strategies help establish a school climate grounded in mutual respect and emotional safety. The results suggest the need for continuous development of teachers’ communication competencies and the integration of anti-violence values into the character education curriculum. Novelty: Further research may explore different educational levels or adopt quantitative approaches to assess the effectiveness of these communication strategies.